The impact of economic crisis on holidays of young people - Chapsa, Xanthippi; Polychronidou, Persefoni (Archives of Business Research, 2018)
Purpose - This work was carried out to investigate the effects of the economic crisis in leisure travel and holidays for young people in Central Macedonia. Methodology - Semi-structured questionnaire was used, combining closed and partially closed questions. Approach - We examined the way in which gender, family situation, and the employment situation affect the travel frequency, the amount spent on travel, the choice and the characteristics of the tourist destination, e.t.c.. Findings - The results show that the answers regarding the travel frequency, the amounts spent on travel, the way in which young people prefer to book their travel, the transportation means, the people they prefer to travel with, the needed time to organize the travel, but also the preferences of the touristic destination and its nightlife, significantly differ between the two genders. Also, marital status seems to be an important differentiating factor of the amounts spent, and preferences regarding the mode of transport, type of accommodation and nightlife.